2008
DOI: 10.1161/strokeaha.107.507475
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal MRI in Cerebral Small Vessel Disease

Abstract: Background and Purpose-Cerebral small vessel disease is the most common cause of vascular dementia. Interest in using MRI parameters as surrogate markers of disease to assess therapies is increasing. In patients with symptomatic sporadic small vessel disease, we determined which MRI parameters best correlated with cognitive function on cross-sectional analysis and which changed over a period of 1 year. Methods-Thirty-five patients with lacunar stroke and leukoaraiosis were recruited. They underwent multimodal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(106 citation statements)
references
References 24 publications
4
101
1
Order By: Relevance
“…A form of magnetic resonance imaging (MRI) called diffusion tensor imaging (DTI) was used to evaluate the structural integrity of the brain white matter at baseline and after 12 mo of thrice-weekly dialysis. DTI was chosen as an imaging modality as it has previously been used to detect clinically significant changes in cerebral small vessel disease [29] . Additionally, MAP extrema points were measured over the course of 12 mo.…”
Section: Effect Of Cooled Dialysate On Vulnerable Vascular Bedsmentioning
confidence: 99%
“…A form of magnetic resonance imaging (MRI) called diffusion tensor imaging (DTI) was used to evaluate the structural integrity of the brain white matter at baseline and after 12 mo of thrice-weekly dialysis. DTI was chosen as an imaging modality as it has previously been used to detect clinically significant changes in cerebral small vessel disease [29] . Additionally, MAP extrema points were measured over the course of 12 mo.…”
Section: Effect Of Cooled Dialysate On Vulnerable Vascular Bedsmentioning
confidence: 99%
“…78 Diffusion tensor imaging changes correlate more closely to cognitive functioning than the volume of visible small-vessel disease-related changes such as WMLs. So far, only few longitudinal studies on the relationship between increase of microstructural damage and cognitive decline are available.…”
Section: Microstructural Changes In Normal-appearing Brain Tissuementioning
confidence: 99%
“…A number of imaging studies using quantitative brain volumetry demonstrated atrophy in both focal and diffuse cerebrovascular diseases [124][125][126][127] . Brain atrophy correlated strongly with the clinical status and cognitive scores, and proved to be a sensitive marker of disease progression in cSVD 104,128,129 . It is now widely accepted that purely subcortical cSVD can lead to cortical volume loss 129,130 .…”
Section: Brain Atrophymentioning
confidence: 84%
“…Accordingly, MD histogram parameters have been reported to correlate more with clinical scores than WMH visual rating scales and volumetric data in cSVD both cross sectionally and longitudinally. Furthermore they were more sensitive than clinical scales in detecting change over time [101][102][103][104][105][106] . There are data indicating that the much simpler, quicker and widely available (DWI) derived ADC can be used similarly to DTI derived MD to quantify brain damage due to cSVD (findings of Gunda et al to be published) (Figure 3 and 4).…”
Section: Evaluation With Non-conventional Mrimentioning
confidence: 99%